Management of Logistics Systems to Increase the Competitiveness of a Community Enterprise Processing Herbs from Local Wisdom in Buriram Province, Thailand - Sirinon, Jantiraporn (Journal of Ecohumanism, 2024)
The objectives of this research are to study: 1) the operating characteristics of the logistics system, 2) the relationship between logistics system management and competitiveness, and 3) development guidelines to increase the competitiveness of a community enterprise processing herbs from local wisdom in Ban Prue Sub-district, Krasang District, Buriram Province. The population and sample consisted of 30 people. Data were collected using a questionnaire and in-depth interviews, as well as group discussions. Data analysis included statistics such as percentage, mean, standard deviation, Pearson correlation coefficient analysis, and multiple regression analysis. The results of the research revealed that: 1) All aspects of logistics system operations were at the highest level. 2) The relationship between logistics system management and competitiveness was at a moderate level, with customer service and packaging management showing a low level of relationship. And 3) development guidelines to increase competitiveness should focus on producing or developing products to have variety and quality, using local wisdom to create trust, acceptance, and reliability in the long term. It should cover all customer needs and emphasize cost leadership by developing the use of resources in a cost-effective manner and determining production costs based on long experience in business operations to reduce costs and increase efficiency. Rapid response should involve developing production according to orders and delivering products to customers on time using modern technology to speed up production. Testing research hypotheses on raw material procurement, inventory management, transportation, and distribution showed a positive impact while packaging management showed a negative impact on competitiveness of the community enterprise processing herbs from local wisdom in Ban Prue Sub-district, Krasang District, Buriram Province. The prediction for the four aspects was at 63.60% (AdjR² = 0.636).